2013
DOI: 10.1002/dmrr.2370
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early diabetic renal changes with hyperpolarized [1‐13C]pyruvate

Abstract: Hyperpolarized (13) C-MRI shows promise in the diagnosis and monitoring of early renal changes associated with diabetes, with the pyruvate/lactate ratio as an imaging biomarker for regional renal changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 13 publications
1
111
1
Order By: Relevance
“…The diabetic kidney is, though, generally hypertrophic with an increased kidney weight early in the development toward diabetic nephropathy. However, this is without substantial alterations in the renal function albeit an increased oxygen consumption (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic kidney is, though, generally hypertrophic with an increased kidney weight early in the development toward diabetic nephropathy. However, this is without substantial alterations in the renal function albeit an increased oxygen consumption (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperpolarization of 13 C-labeled molecules remarkably enhances its sensitivity and allows noninvasive investigation of dynamic metabolic processes of the substrates. Using a hyperpolarized [1- 13 C]pyruvate, Laustsen et al has shown that reduction of inspired oxygen increases renal lactate and alanine formation in diabetic mice, while this effect is not observed in non-diabetic controls [41, 42], indicating that reduced oxygen availability alters renal energy metabolism in diabetes. Further, Keshari et al has assessed the oxidative stress in diabetic mouse kidneys using a hyperpolarized [1- 13 C] dehydroascorbate (DHA), a new endogenous redox sensor, and shown that redox capacity is decreased in diabetic kidneys prior to histological evidence of nephropathy and that angiotensin converting enzyme inhibition restores the renal redox status in diabetic mice [43].…”
Section: Assessment Of Renal Metabolismmentioning
confidence: 99%
“…The observable conversion of HP substrate [1][2][3][4][5][6][7][8][9][10][11][12][13] C]pyruvate to HP [1-13 C]lactate catalyzed by lactate dehydrogenase (LDH) has generated particular interest as a glycolytic marker, with promising applications in cancer (4), cardiovascular disease (5,6), and diabetes (7), including a recent "first-in-man" HP 13 C MRI clinical Phase 1 safety trial in prostate cancer patients (8).…”
Section: Introductionmentioning
confidence: 99%